Řekni mi, kde to bolí, a já ti řeknu, jaký jsi člověk: funkce bolesti v klasické řecké filosofii a lékařství. - LINKA, VOJTĚCH (Filozofia, 2024)
In this article, I explore the role of pain in ancient Greek medicine and philosophy, focusing on the period from the 5th century BC to the end of the 4th century BC. I analyze how Greek physicians, perceived pain and its significance in understanding the human body, diagnosis, and treatment. Additionally, I show that this framework for comprehending pain is also present in the philosophies of Plato and Aristotle. Despite initial differences in approach, both physicians and philosophers aim to understand, incorporate, and potentially utilize pain for beneficial purposes, given its inherent connection to certain positive aspects of human life. This article not only addresses the specific issue of pain in ancient medicine and philosophy but also examines the relationship between these two domains of human knowledge and practice.